Vitamin D supplementation for children with cancer: A systematic review and consensus recommendations. (8th June 2021) - van Atteveld, Jenneke E.; Verhagen, Iris E.; van den Heuvel‐Eibrink, Marry M.; van Santen, Hanneke M.; van der Sluis, Inge M.; Di Iorgi, Natascia; Simmons, Jill H.; Ward, Leanne M.; Neggers, Sebastian J.C.M.M.
Abstract: Background: Prevalent vitamin D deficiency (VDD) and low bone mineral density (BMD) have led to vitamin D supplementation for children with cancer, regardless vitamin D status. However, it remains unsettled whether this enhances bone strength. We sought to address this issue by carrying out a systematic review of the literature. Methods: We conducted a literature search using PubMed, Embase, and Cochrane databases. Studies including children up to 5 years after cancer therapy were assessed for the association between 25‐hydroxyvitamin D (25OHD) levels and BMD Z ‐scores or fractures, and the effect of vitamin D supplementation on BMD or fractures. Evidence quality was assessed using the GRADE methodology. Results: Nineteen studies (16 observational and 3 interventional, mainly involving children with hematologic malignancies) were included. One study which analyzed 25OHD as a threshold variable (≤10 ng/ml) found a significant association between 25OHD levels and BMD Z ‐scores, while 25OHD as a continuous variable was not significantly associated with BMD Z ‐scores in 14 observational studies. We found neither a significant association between lower 25OHD levels and fractures (2 studies), nor between vitamin D (and calcium) supplementation and BMD or fracture frequency (3 studies) (very low quality evidence). Conclusion: There is a lack of evidence for an effect of vitamin D (and calcium) supplementation on BMD or fractures in children with cancer. Further research is needed; until then, we recommend dietary vitamin D/calcium intake in keeping with standard national guidelines, and periodic 25OHD monitoring to detect levels <20 ng/ml. Vitamin D/calcium supplementation is recommended in children with low levels, to maintain levels ≥20 ng/ml year‐long. Abstract : The relationship between 25OHD levels and BMD or fractures has been inadequately studied, and there is lack of evidence for an effect of universal vitamin D supplementation on BMD or fractures in children with cancer. Further research is needed; we provide recommendations to ensure 25OHD levels adequate for bone health in this population based on the current very low quality evidence and expert opinion. ​